2012
DOI: 10.1002/jcp.24086
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate induces apoptosis via a Bak‐mediated caspase‐independent intrinsic pathway in human lung adenocarcinoma cells

Abstract: This report is designed to explore the exact molecular mechanism by which artesunate (ART), a semisynthetic derivative of the herbal antimalaria drug artemisinin, induces apoptosis in human lung adenocarcinoma (ASTC-a-1 and A549) cell lines. ART treatment induced ROS-mediated apoptosis in a concentration- and time-dependent fashion accompanying the loss of mitochondrial potential and subsequent release of Smac and AIF indicative of intrinsic apoptosis pathway. Blockage of casapse-8 and -9 did not show any inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 54 publications
5
70
1
Order By: Relevance
“…Similar to DHA, ARTS induces caspase-dependent intrinsic apoptosis in many cancer cell lines such as Leukemic T cells, Neuroblastoma and Pancreatic cancer cells [2,[33][34][35]. However, we recently found that caspase-independent intrinsic pathway played an important role in ARTSinduced apoptosis of both A549 and ASTC-a-1 cell lines [36]. NF-jB pathway may be involved in ARTS-induced multiple myeloma cell apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to DHA, ARTS induces caspase-dependent intrinsic apoptosis in many cancer cell lines such as Leukemic T cells, Neuroblastoma and Pancreatic cancer cells [2,[33][34][35]. However, we recently found that caspase-independent intrinsic pathway played an important role in ARTSinduced apoptosis of both A549 and ASTC-a-1 cell lines [36]. NF-jB pathway may be involved in ARTS-induced multiple myeloma cell apoptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-dependent intrinsic pathway [2,[33][34][35] NSCLC (A549, ASTC-a-1) Caspase-independent intrinsic pathway [36] Breast cancer (MCF-7, T47D) Lysosome-dependent intrinsic pathway [35] Multiple myeloma (SP2/0) Decreased NF-jB pathway [37] ARTE Hepatoma (HepG2, Hep3B)…”
Section: Nomentioning
confidence: 99%
“…Artesunate, is a derivative of artemisinin isolated from Artemisia annua L, has been used to treat malaria, especially against cerebral malaria (Padilla-Camberos et al, 2010;Bachmeier et al, 2011;Berdelle et al, 2011;Jin et al, 2011;Mota et al, 2011;Jiang et al, 2012;Zhou et al, 2012), new report shown that it has a variety of biological activities, such as hepatoprotective, antioxidative, antiinflammatory, antidiabetic, antiallergic, and antibacterial effects (Li et al, 2009;Bat-Chen et al, 2010;Du et al,…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is an increasing amount of evidence suggesting that ART has an anti-cancer function (3). For instance, ART has been shown to induce apoptosis and necrosis in multiple human cancer cells (4,5). The anti-cancer effects of ART also include the following: cell cycle arrest (6), inhibition of angiogenesis (7), and reduction of cell invasion and metastasis (8).…”
mentioning
confidence: 99%